Echoes from the past: Regional variations in recovery within a harbour seal population - Brasseur, Sophie M. J. M.; Reijnders, Peter J. H.; Cremer, Jenny; Meesters, Erik; Kirkwood, Roger; Jensen, Lasse Fast; Jeβ, Armin; Galatius, Anders; Teilmann, Jonas; Aarts, Geert (PLOS ONE, 2018)
Terrestrial and marine wildlife populations have been severely reduced by hunting, fishing and habitat destruction, especially in the last centuries. Although management regulations have led to the recovery of some populations, the underlying processes are not always well understood. This study uses a 40-year time series of counts of harbour seals (Phoca vitulina) in the Wadden Sea to study these processes, and demonstrates the influence of historical regional differences in management regimes on the recovery of this population. While the Wadden Sea is considered one ecologically coupled zone, with a distinct harbour seal population, the area is divided into four geo-political regions i.e. the Netherlands, Lower Saxony including Hamburg, Schleswig-Holstein and Denmark. Gradually, seal hunting was banned between 1962 and 1977 in the different regions. Counts of moulting harbour seals and pup counts, obtained during aerial surveys between 1974 and 2014, show a population growth from approximately 4500 to 39,000 individuals. Population growth models were developed to assess if population growth differed between regions, taking into account two Phocine Distemper Virus (PDV) epizootics, in 1988 and 2002 which seriously affected the population. After a slow start prior to the first epizootic, the overall population grew exponentially at rates close to assumed maximum rates of increase in a harbour seal population. Recently, growth slowed down, potentially indicative of approaching carrying capacity. Regional differences in growth rates were demonstrated, with the highest recovery in Netherlands after the first PDV epizootic (i.e. 17.9%), suggesting that growth was fuelled by migration from the other regions, where growth remained at or below the intrinsic growth rate (13%). The seals’ distribution changed, and although the proportion of seals counted in the German regions declined, they remained by far the most important pupping region, with approximately 70% of all pups being born there. It is hypothesised that differences in hunting regime, preceding the protection in the 1960’s and 1970’s, created unbalance in the distribution of breeding females throughout the Wadden Sea, which prevailed for decades. Breeding site fidelity promoted the growth in pup numbers at less affected breeding sites, while recolonisation of new breeding areas would be suppressed by the philopatry displayed by the animals born there. This study shows that for long-lived species, variable management regimes in this case hunting regulations, across a species’ range can drive population dynamics for several generations.